A aplicação e a exigibilidade das astreintes no Processo Civil Brasileiro - Marino, Luana Salvador (2014)
The work has as its central theme the application and enforceability of astreintes the Brazilian Civil Procedure. Addresses the issue of penalty in the legal system , as well as the current legislative forecast, also analyzing the aspects and effects of the court decision to impose . Discusses the final decision on the merits of dismissal and its implication in the enforceability of credit resulting from the impact of the fine and the end comes the enforceability of astreintes , a case of provisional or final execution